MAC OS X Leopard beyond the manual - Meyers, Scott, 1968-; Lee, Mike.; Safari eBooks (Berkeley, [Calif.] : Apress, 2008)
Designed for sophisticated computer users, an overview of the latest version of Leopard examines the all new features, as well as those that, although previously available in earlier versions of OS X, had not been easily accessible, covering such areas as changes to the user interface, iCal, Boot Camp, Dashboard, Spotlight, Mail, and Time Machine.
Getting to know Leopard -- Customizing and administering Leopard -- Communications and the Internet -- Working with applications -- Getting to know Darwin -- Networking Leopard -- Leopard development and scripting -- Cross-platform solutions.
Includes index.
Electronic reproduction.
Keywords: Mac OS; Operating systems (Computers); Macintosh (Computer) -- Programming; Electronic books